Efeito do cruzamento entre diferentes genótipos para o uso em sistemas alternativos de frangos de corte - Brum, Olmiro Bochi (2005)
The powerful influence of the consumer on the productivity chain and also in broiler chicken production makes clear that, parallel to large-scale production, it exists an open market originated from habits changes of part of the population, who are of a higher purchasing power and are in search of food that are originated from a natural production process, with a differential in meat quality referring to its texture, color and flavor. These have stimulated small and median producers who do not have neither physical nor economic structure to compete with the industrial system, to think towards an alternative production of broiler chickens. Aiming at finding out new alternatives for the breeding of poultry specially selected to the alternative breeding of broiler chicken, an experiment was carry out in the Poultry Department of the Federal University of Santa Maria and in the Vale do Jaguari Technological Center at URI Campus Santiago, the methodology used was the use of progeny from crosses between broiler breeder male X Rhodes Island Red female, broiler breeder male X Plymouth Rock White female, broiler breeder male X Plymouth Rock Barred female, Rhodes Island Red male X broiler breeder female, Plymouth Rock White male X broiler breeder female and Plymouth Rock Barred male X broiler breeder female representing treatments T1, T2, T3, T4, T5 and T6 respectively, focusing on the evaluation of crossings in the performance of broilers. It was analyzed the corporeal weight at 1, 21, 42 ad 56 days of age, the average weight gain, ration consumption, nourishment viability and conversion at the periods of 1 to 21, 22 to 42, 43 to 56 and from 1 to 56 days of age, profit and carcass weight, legs (drumsticks and thighs), and breast with kill between 49 to 56 days of age. The experimental outline was purely casual centered with six treatments, each treatment consisting of six repetitions and each experiment unit formed of 18 broilers between 1 to 56 days old. The collected data was tests under variance analysis and significant differences with a 5% level of probability were tested using the Tukey test. We verified significant differences between treatments referring to corporal weight, average weigh gain and food consumption in all periods tested and to nourishing conversion at the periods of 1 to 21, 22 to 42 and 1 to 56 days old broilers. Although the carcass weigh was significantly influenced at 49 and 56 days when carcass profit and breast weight were analyzed no significant difference (P>0,05) was verified but to legs weight, however, significant differences between treatments were shown only for kill at 56 days old.